Artificial intelligence and the future of creativity: transforming practice and principles in art and design - Gurieva, N.; Gutierrez Abril de la Rosa (ТОВ «Видавництво Ліра-К», 2025)
Our research explores the future of digital art in the age of artificial intelligence, viewing the field as an important lens for examining broader trends in the worlds of art and technology
Keywords: digital art